Paradigms, values and education (Educação e Pesquisa, 2009)
The text draws the epistemological and socioanalytic profiles of the paradigmatic question. Mauss evinced the moule affectif of the scientific notions of force and cause. Later, Baudouin would speak of the archetypical induction of the notions, and Durand's anthropology of the imaginary would conclude for the archetypical induction of the concept by the image. That was the unveiling of the unconscious substrate of ideations, of a substrate governed by the vectorialized cathexis translated into values as the kernel of ideations. It is the famous emotive a priori. The text therefore questions two myths, mainstays of classical science: the myth of scientific objectivity, and that of axiological neutrality. It brings forward the fallacy of the existence of an epistemological rupture between science and ideology. Henceforth, ideations become ideologies, particularly in the sciences of Man and in the sciences of education which, in addition to that, are made to give support to a hidden ideological struggle in which the knowledge strategies, in a "cognitive colonialism", conceal those of prejudice. At any rate, assuming the reality of this phantasmanalytic and ideological support allows a salutary educative task: paradigms become fantasies and, in this critical relativization, can be used as a field of collective transitional objects in a cultural and educative gameness. In the polyculturalism of contemporary society, Weber's "polytheism of values" becomes an "epistemological polytheism" governed by Feyerabend's "ontological relativism" and by an ethics of pragmatism. Articulating culture, organization and education, the anthropology of educational organizations and the group culturanalysis of Paula Carvalho represent the heuristics of this transitional dialectics.